2017
DOI: 10.1007/s10930-017-9697-y
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Pistil Responses to Incompatible and Compatible Pollen in Self-Incompatibility Brassica oleracea Using Comparative Proteomics

Abstract: Angiosperms have developed self-incompatibility (SI) systems to reject self-pollen, thereby promoting outcrossing. The Brassicaceae belongs to typical sporophytic system, having a single S-locus controlled SI response, and was chosen as a model system to study SI-related intercellular signal transduction. In this regard, the downstream factor of EXO70A1 was unknown. Here, protein two-dimensional electrophoresis (2-DE) method and coupled with matrix-assisted laser desorption ionization/time of flight of flight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…a b that the interaction between SRK7 kinase domain and CaM12 depended on its four EF-hand domains (Xu et al, 2013). Proteomics analysis revealed that the protein profile in the pistil changed after either compatible or incompatible pollination at 1 h (Chen et al, 2013;Zeng et al, 2017). In GST pull down assay, we separated one specific band located between 130-180 kDa size in the pistil proteins + GST-CML27 lane.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…a b that the interaction between SRK7 kinase domain and CaM12 depended on its four EF-hand domains (Xu et al, 2013). Proteomics analysis revealed that the protein profile in the pistil changed after either compatible or incompatible pollination at 1 h (Chen et al, 2013;Zeng et al, 2017). In GST pull down assay, we separated one specific band located between 130-180 kDa size in the pistil proteins + GST-CML27 lane.…”
Section: Discussionmentioning
confidence: 95%
“…A number of molecular components in the selfincompatibility signaling pathway have been identified in both pollen and the pistil organs (Stone et al, 2003;Takasaki et al, 2000;). For further investigated potential candidate genes involved in self-incompatibility, RNA-sequence and proteomics were explored to study pistil molecules in the pollination process (Samuel et al, 2011;Zhang et al, 2015;Zeng et al, 2017). The mRNA levels of key regulatory components in the selfincompatibility signaling pathway, including the levels in SRK and ARC1 have been shown to increase during the initial 30 min, followed by a reduction at 1 h after pollination .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Brassica oleracea is also considered to be a model for the study of the genomic evolution of Brassica species due to its typical diploid genome structure [ 26 ]. The molecular mechanisms underlying many significant biological processes, including pigment accumulation [ 27 ], self-incompatibility [ 28 ], and flowering [ 29 ], have been dissected in Brassica oleracea , while a lot of classic biotechnologies, including virus-induced gene silencing (VIGS) [ 30 ] and CRISPR/Cas9-based gene editing [ 31 ], have also been applied in Brassica oleracea . Thus, the discovery of functional genes in Brassica oleracea is required for the genetic improvement of desired traits by the most advanced molecular breeding strategies.…”
Section: Introductionmentioning
confidence: 99%